The Methodology of Imam Ash‘ari in Engaging with Sifat Khabariyyah Through the Book al-Ibanah - Mohd Saiba Yaacob; Syed Hadzrullathfi Syed Omar; Engku Ibrahim Engku Wok Zin (Rabbanica: Journal of Revealed Knowledge)
Imam Abu al-Hasan al-Ash‘ari (Imam Ash‘ari) produced various works that discuss the authentic manhaj (methodology) of engaging with Sifat Khabariyyah. He adopted two distinct approaches through different writings: the Ithbat and Tafwid. Among the challenges that arose were the differing views of later scholars regarding Imam Ash‘ari’s final manhaj. This led proponents of sect Ithbat to question the sect of Tafwid and vice versa. Unlike the phenomenon of ikhtilaf, this study seeks to identify the manhaj (methodology) adopted by Imam Ash‘ari in his work, al-Ibanah, by referencing three distinct text versions. This research aims to ascertain the concepts and principles of Ithbat that Imam Ash'ari affirmed in al-Ibanah. The study employs a qualitative approach, applying library research techniques, including data collection and analysis. The findings indicate that in al-Ibanah, Imam Ash‘ari adopted the manhaj al-Ithbat bi-la Kayfiyyah, affirming attributes like istiwa’, nuzul, wajh, yad, ‘ayn, and curb, while negating al-hudud, such as corporeality, physical composition, spatial location, movement or displacement, sitting, and other similar traits. These findings can serve as a foundation for reconciling the sects of Ithbat and Tafwid, thereby strengthening the Muslim community's comprehension of the categorisation of Ahl al-Sunnah wa al-Jama‘ah scholars into three groups: Ahl al-Hadith, Ash‘ariyyah, and Maturidiyyah.